Anxiolytic activity of Indian Hypericum perforatum Linn: An experimental study - Kumar V.; Jaiswal A.K.; Singh P.N.; Bhattacharya S.K. (My University, 2025)
The putative anxiolytic activity of 50 % ethanolic extract of Indian Hypericum perforatum (IHp) was investigated in rats using various experimental paradigms of anxiety viz. open field exploratory behaviour (OFB), elevated plus maze (EPM), elevated zero maze (EZM), novelty induced suppressed feeding latency (FL) and social interaction (SI) tests. Pilot studies indicated that single dose administration of IHp had little to no acute behavioural effects, hence the extract of IHp was administered orally at different dose levels once daily for three consecutive days, while lorazepam (LR) (0.5 mg/kg, ip) was administered acutely. IHp extract (100 and 200 mg/kg, po) showed significant anxiolytic effects on all the paradigms of anxiety. The results indicate that IHp and LR induced a significant increase in open field ambulation and slight increase in rearings and activity in centre, whereas grooming and fecal droppings remain unchanged. In EPM, significant augmentation of open arm entries, open arm/closed arm entries ratio and time spent on open arms was noted in IHp treated rats. In EZM test, significant increase in time spent on open arms and entries in open arms were observed, whereas slight increase in head dips and stretched attend postures were also observed. IHp and LR significantly attenuated the novelty induced increase in feeding latency. IHp treated rats also showed significant increase in social interaction in the novel environment. The IHp extracts showed consistent and significant anxiolytic activity in all the tests. The effects induced by 50 % ethanolic extract of IHp were less marked than those of lorazepam were.